Stronger Security Proofs for RSA and Rabin Bits - Fischlin, R.; Schnorr, C. P. (Journal of cryptology, 2000)
The RSA and Rabin encryption functions are respectively defined as EN(x) = xe mod N and EN(x) = x2 mod N , where N is a product of two large random primes p , q and e is relatively prime to φ (N) . We present a simpler and tighter proof of the result of Alexi et al. [ACGS] that the following problems are equivalent by probabilistic polynomial time reductions: (1) given EN(x) find x; (2) given EN(x) predict the least-significant bit of x with success probability 1/2 + 1/poly(n) , where N has n bits. The new proof consists of a more efficient algorithm for inverting the RSA/ Rabin function with the help of an oracle that predicts the least-significant bit of x . It yields provable security guarantees for RSA message bits and for the RSA random number generator for modules N of practical size.